Forest biodiversity increases productivity via complementarity from greater canopy structural complexity - Xianglu Deng; Bernhard Schmid; Helge Bruelheide; Chen Chen; Yi Li; Shan Li; Felix Morsdorf; Tama Ray; Meredith C. Schuman; Ting Tang; Goddert von Oheimb; Keping Ma; et al. (Proceedings of the National Academy of Sciences, 2025)
The horizontal distribution and vertical stratification of tree crowns can affect light interception and tree growth, thus driving forest productivity and carbon storage. However, how canopy structure is affected by tree diversity and thus can mediate its effects on productivity remains unclear. Using 4-y consecutive unmanned aerial vehicle-borne light detection and ranging and ground-based growth measurements from 482 plots and 38,088 trees, 11 to 15 y after planting, within a large-scale forest biodiversity experiment in southeast China, we found that increased canopy structural complexity consistently explains the positive effects of tree diversity on productivity. Species complementarity was the main mediator of diversity-enhanced productivity, with the positive complementarity effects strengthening over time. Our study underscores the importance of establishing multispecies forest communities with complex canopy structure to maximize productivity and carbon sequestration in forest ecosystems.